OP0343 The intestinal involvement in systemic sclerosis is characterized by a peculiar gut microbiota. (15th June 2017) - Natalello, G; Bosello, SL; Sterbini, F Paroni; Palladini, A; Canestrari, GB; Parisi, F; Lorenzis, E De; Berardi, G; Posteraro, B; Sanguinetti, M; Ferraccioli, G
Abstract : Background: Gastrointestinal involvement is recognized as a major cause of morbidity and mortality in Systemic Sclerosis (SSc) and its pathophysiology is still unclear. Few data on composition and function of gut microenvironment in SSc are reported in the literature but there is a growing body of evidences supporting the hypothesis of a relation between gut microbiota and the host immune system. Objectives: The goal of this study was to characterize fecal microbiota in SSc patients compared to healthy subjects to investigate whether specific microbial species may be responsible of dysbiosis in SSc. Furthermore, we investigated the composition of microbiota in the different clinical subsets of SSc. Methods: Faecal samples were obtained from 17 healthy controls and 39 SSc patients including subjects with different skin involvement (Diffuse and Limited) and disease duration. The BMI was normal and the mean age was similar both in SSc and controls groups. The composition of microbiota was determined through 16S rRNA pyrosequencing performed using the GS Titanium technology. Rarefaction was used to uniform abudance data. α-diversity was defined by the main indexes while β-diversity was determined according to Bray-Curtis and UniFrac, represented trough Principal Coordinate Analysis (PCoA) and compared using PERMANOVA test on distance matrices. Linear Discriminant Analysis Effect Size was used to identify taxa that showed differential expression between the groups. Results: At genus level SSc patients showed a differential expression in 12 taxa compared to controls with higher levels of Ruminococcus, Streptococcus, Lactobacillus, Blautia, Coprococcus and Phascolarctobacterium and a depletion of Bacteroides, Butyciromonas, Odoribacter, Succinivibrio, Sutterella and Prevotella . The differences in microbiota composition between SSc patients and controls were supported also by PCoA of the values representing phylogenetic distance of microbial communities between specimens (p<0.001) (see figure). Among scleroderma patients, those with diffuse skin involvement showed a greater abundance of bacteria of Bacteroidetes phylum with significantly lower values of alpha diversity by Chao1 and species richness (p=0.01). Differences were confirmed by PERMANOVA on Bray-Curtis distance matrix (p=0.016). Conclusions: Our analysis demonstrated an altered and distinct composition of gut microbiota in SSc patients compared to healthy controls. Furthermore, scleroderma patients show some differences in microbiota characteristics according to the extent of skin involvement, suggesting that microbiota may influence the severity of the disease. If validated and related to GI symptomathology and nutritional status our findings open up the opportunity of a rational intervention on microbiota to restore the gut equilibrium in SSc patients. Disclosure of Interest: None declared